A comprehensive meta-analysis of character education programs. Issue 2 (3rd April 2023) - Brown, Mitch; McGrath, Robert E.; Bier, Melinda C.; Johnson, Keith; Berkowitz, Marvin W.
ABSTRACT: This study represents a large meta-analytic investigation of character education studies. We identified 214 studies up until 2017 ( NTotal  = 307, 512) with at least one computable effect size comparing a character education program to a control condition. Initial analyses indicated a small, significant average positive effect for character education ( g = 0.24, 95% CI [0.19, 0.28]). Single-session interventions and mentoring programs were associated with larger effects. However, all treatment lengths were associated with significant treatment effects, and the number of single-session interventions was small. Three programs—Cognitive Problem-Solving, Kohlberg's Moral Dilemma Discussion and Strong Kids—were associated with above-average effects in multiple assessments. Evidence emerged suggesting selection bias in published literature. Correcting this bias indicated lower estimates of mean effects while remaining positive and significant. We consider heterogeneity in reporting standards and discuss how to address biases.